Intracerebral efficacy and tolerance of nivolumab in non–small-cell lung cancer patients with brain metastases. (February 2018) - Gauvain, Clément; Vauléon, Enora; Chouaid, Christos; Lerhun, Emilie; Jabot, Laurence; Scherpereel, Arnaud; Vinas, Florent; Cortot, Alexis Benjamin; Monnet, Isabelle
Highlights: Nivolumab can be used to treat NSCLCs patients with brain metastases. Nivolumab intracerebral and extracerebral response and control ratesare similar in these patients. NSCLC patients with brain metastases and treated by nivolumab have an acceptable nivolumab safety profile. Abstract: Objectives: Although nivolumab has shown efficacy against non–small-cell lung cancers (NSCLCs), patients with active brain metastases (BMs) were excluded from pivotal clinical trials. Hence, data regarding nivolumab intracerebral activity and safety in NSCLC patients with BMs are scarce. Materials and methods: We conducted a retrospective multicenter study on NSCLC patients with BMs treated with nivolumab. The primary endpoint was intracerebral objective response rate (IORR), according to RECIST criteria. Secondary endpoints included intracerebral control rate, intracerebral and general progression-free survival (PFS), overall survival (OS) and tolerance. Results and conclusion: Forty-three patients were included. BMs were locally pretreated in 34 (79%) patients and active in 16 (37%) patients. Median follow-up was 5.7 (95% CI: 2.7–8.4) months. IORR and extracerebral response rate were, respectively, 9% (95% CI: 3–23%) and 11% (95% CI: 4–26%). Intracerebral control rate was 51% (95% CI: 37–66%). Median intracerebral and general PFS lasted 3.9 (95% CI: 2.8–11.1) and 2.8 (95% CI: 1.8–4.6) months, respectively. Median OS was 7.5 (95% CI: 5.6–not reached) months. Five neurological adverse events occurred, including 1 grade-4 transient ischemic attack of uncertain imputability and 1 grade-3 neurological deficit; neither required nivolumab discontinuation. Nivolumab intracerebral activity was similar to its reported extracerebral efficacy, with an acceptable safety profile. Prospective and controlled data are needed to determine nivolumab's place in treatment of NSCLC patients with BMs.